Size Effects of the Anions in the Ionothermal Synthesis of Carbon Nitride Materials. Issue 33 (2nd May 2022) - Burmeister, David; Müller, Johannes; Plaickner, Julian; Kochovski, Zdravko; List‐Kratochvil, Emil J. W.; Bojdys, Michael J.
Abstract: Semiconducting carbon nitride polymers are used in metal‐free photocatalysts and in opto‐electronic devices. Conventionally, they are obtained using thermal and ionothermal syntheses in inscrutable, closed systems and therefore, their condensation behavior is poorly understood. Here, the synthetic protocols and properties are compared for two types of carbon nitride materials – 2D layered poly(triazine imide) (PTI) and hydrogen‐bonded melem hydrate – obtained from three low‐melting salt eutectics taken from the systematic series of the alkali metal halides: LiCl/KCl, LiBr/KBr, and LiI/KI. The size of the anion plays a significant role in the formation process of the condensed carbon nitride polymers, and it suggests a strong templating effect. The smaller anions (chloride and bromide) become incorporated into triazine (C3 N3 )‐based PTI frameworks. The larger iodide does not stabilize the formation of a triazine‐based polymer, but instead it leads to the formation of the heptazine (C6 N7 )‐based hydrogen‐bonded melem hydrate as the main crystalline phase. Melem hydrate, obtained as single‐crystalline powders, was compared with PTI in photocatalytic hydrogen evolution from water and in an OLED device. Further, the emergence of each carbon nitride species from its corresponding salt eutectic was rationalized via density functional theory calculations. This study highlights the possibilities to further tailor the properties of eutectic salt melts for ionothermal synthesis of organic functional materials. Abstract : Size effects : Ionothermal condensation of dicyandiamide in alkali halide salt melts leads to the formation of extended 2D, layered frameworks only in the presence of small halides such as chloride, and bromide. With increasing size of the alkali halide intercalate, stabilizing van der Waals interactions between extended, π‐conjugated triazine‐based sheets are lost. The main, crystalline product from an alkali iodide eutectic was identified as melem hydrate, a heptazine (C6 N7 )‐based, hydrogen‐bonded, monoclinic solid.